Both resistance training and aerobic training reduce hepatic fat content in type 2 diabetic subjects with nonalcoholic fatty liver disease (the RAED2 randomized trial). Issue 4 (22nd August 2013) - Bacchi, Elisabetta; Negri, Carlo; Targher, Giovanni; Faccioli, Niccolò; Lanza, Massimo; Zoppini, Giacomo; Zanolin, Elisabetta; Schena, Federico; Bonora, Enzo; Moghetti, Paolo
<x xml:space="preserve">Abstract</x> Although lifestyle interventions are considered the first‐line therapy for nonalcoholic fatty liver disease (NAFLD), which is extremely common in people with type 2 diabetes, no intervention studies have compared the effects of aerobic (AER) or resistance (RES) training on hepatic fat content in type 2 diabetic subjects with NAFLD. In this randomized controlled trial, we compared the 4‐month effects of either AER or RES training on insulin sensitivity (by hyperinsulinemic euglycemic clamp), body composition (by dual‐energy X‐ray absorptiometry), as well as hepatic fat content and visceral (VAT), superficial (SSAT), and deep (DSAT) subcutaneous abdominal adipose tissue (all quantified by an in‐opposed‐phase magnetic resonance imaging technique) in 31 sedentary adults with type 2 diabetes and NAFLD. After training, hepatic fat content was markedly reduced (P < 0.001), to a similar extent, in both the AER and the RES training groups (mean relative reduction from baseline [95% confidence interval] −32.8% [−58.20 to −7.52] versus −25.9% [−50.92 to −0.94], respectively). Additionally, hepatic steatosis (defined as hepatic fat content >5.56%) disappeared in about one‐quarter of the patients in each intervention group (23.1% in the AER group and 23.5% in the RES group). Insulin sensitivity during euglycemic clamp was increased, whereas total body fat mass, VAT, SSAT, and hemoglobin A1c were reduced comparably in both intervention groups. Conclusion: This is the first randomized controlled study to demonstrate that resistance training and aerobic training are equally effective in reducing hepatic fat content among type 2 diabetic patients with NAFLD. (Hepatology 2013;58:1287–1295)